2008
DOI: 10.1021/jf800832r
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins: Target Compounds as Antibacterial Agents

Abstract: Grape seeds accumulate in huge quantities as byproduct during wine production and are therefore a cheap source for pharmacologically active agents. However, studies prove poor antibacterial activity, and results of analyses are sometimes contradictory. The aim of this study was, thus, to determine the antibacterial activity of grape seed extracts with special focus on the chromatographic characterization of active fractions. In the course of these investigations, extraction protocols were optimized so that mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
62
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(66 citation statements)
references
References 29 publications
3
62
1
Order By: Relevance
“…But, the flavonoids are poorly absorbed in the intestines and their concentration in target tissues are very low to perform its role as antioxidant defenses (Surai, 2014). Grape (Vitis Vinifera) seeds are a good source of polyphenolic compounds which have been appeared to have different useful pharmacological impacts, including anti-hyper lipidemic (Moreno et al, 2003), anti-bacterial activities (Mayer et al, 2008) and anti-inflammatory (Terra et al, 2009). Shi et al (2003) reported that the antioxidant potential of GS is 20 and 50 fold higher than Vit.…”
Section: Introductionmentioning
confidence: 99%
“…But, the flavonoids are poorly absorbed in the intestines and their concentration in target tissues are very low to perform its role as antioxidant defenses (Surai, 2014). Grape (Vitis Vinifera) seeds are a good source of polyphenolic compounds which have been appeared to have different useful pharmacological impacts, including anti-hyper lipidemic (Moreno et al, 2003), anti-bacterial activities (Mayer et al, 2008) and anti-inflammatory (Terra et al, 2009). Shi et al (2003) reported that the antioxidant potential of GS is 20 and 50 fold higher than Vit.…”
Section: Introductionmentioning
confidence: 99%
“…Condensed tannins are known as proanthocyanidins, which are the most abundant flavonoids present in GSE. 13 GSE demonstrated the strongest antioxidant effects and free radical scavenging ability 14 as well as being anti-inflammatory, 15 anticancer, 16 antibacterial 17 ; it has platelet aggregation inhibiting and metal chelating properties 18 and vasodilatory, immunostimulating, antiallergic, antiviral activates 19 ; it reduced plasma cholesterol in animals fed a high cholesterol diet and that may reduce risk of atherosclerosis. 20 Recently, GSE has been marketed as dietary supplement and advocated for its multiple beneficial properties.…”
Section: Introductionmentioning
confidence: 99%
“…In grape seeds, proanthocyanidins were determined as active antibacterial agents toward 10 different pathogenic Gram-positive and Gram-negative bacterial strains. 30 Plant-derived proanthocyanidins may inhibit the growth of pathogenic bacteria by binding strongly to proteins at bacterial cell surfaces. 31 In this research we revealed that PABE at the concentration 200 mg ml -1 showed bactericidal activity against two MDR clinical isolates of A. baumannii belonging to EU clone I and II and antibacterial activity at lower concentrations, in vitro.…”
Section: Resultsmentioning
confidence: 99%